Leveraging GIS and spatial analysis for informed decision-making in COVID-19 pandemic. Issue 1 (March 2021) - Ahasan, Rakibul; Hossain, Md Mahbub
Highlights: Geographic Information System (GIS) techniques are widely used across scientific disciplines, including public health since the mid-1960s. GIS has been playing a critical role in understanding the spatial clustering and transmission trend of the ongoing COVID-19. The Johns Hopkins University created a near-real-time GIS-based COVID-19 case tracking and documentation mechanism. Applications of GIS in COVID-19 related studies were focused on mapping the cases on different administrative units. GIS could be used to predict not only the confirmed case numbers but also specific locations where the outbreak would happen with a higher statistical precision.